Investigating the antecedents of halal brand product purchase intention: an empirical investigation. Issue 7 (22nd May 2020) - Ali, Afzaal; Sherwani, Mehkar; Ali, Adnan; Ali, Zeeshan; Sherwani, Mariam
Abstract : Purpose: This paper aims to apply the concept of traditional branding constructs, i.e. brand image, brand perceived quality, brand satisfaction, brand trust and brand loyalty to a less explored field of halal brand products – halal brand image, halal brand perceived quality, halal brand satisfaction, halal brand trust and halal brand loyalty. Second, the present research is an effort to empirically validate the interrelationships among branding constructs such as brand image, brand perceived quality, brand satisfaction, brand trust and brand loyalty in a holistic framework to confirm whether these branding constructs also work for the halal brand in the same way to gauge Chinese Muslims consumers' purchasing intentions. Design/methodology/approach: This research used cross-sectional data from 481 Chinese Muslim students at 9 universities located in 3 cities of China through face-to-face and online survey methods. Data were collected from the consumers of halal milk brand. A theoretical model with the hypothesized relationships was tested with the help of the structural equation modelling procedure. Findings: The results suggest that halal brand image has a significant and positive influence on the halal brand perceived quality, halal brand satisfaction, halal brand trust and halal brand loyalty. Similarly, the halal brand perceived quality, halal brand satisfaction, halal brand trust and halal brand loyalty significantly influence consumer halal brand purchase intention. Research limitations/implications: This study is conducted in the halal food sector of China and specific religious and migration contexts. Further investigations of the halal food purchasing behaviour of local Muslims, as well as international Muslim students in those Western countries which are famous destinations for international students for education, could yield varying results. Practical implications: The outcomes achieved are helpful for commerce and government organizations for policy development to better meet the burgeoning demand for halal products by Chinese Muslims. These are also very helpful for producers and exporters who intend to penetrate the halal market in non-Muslim-dominant countries such as China. Originality/value: Studies on understanding Muslim consumers' purchasing behaviours in non-Muslim countries are limited. Given the fact, numbers of Muslims seem a smaller amount of China's total population, but their total numbers are large compared with total numbers in many Muslim countries. Therefore, understanding their purchasing behaviours for halal products and influential determinants concerning such purchasing behaviours adds to the literature and helps the industry to better serve and capitalise on the growing market.